Pendampingan Budaya Kerja 6s dalam Industri Sepatu untuk Meningkatkan Kerapian dan Keselamatan Kerja - Luthfiah Nur Fatikha; Ary Kusmanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The implementation of the 6S work culture (Seiri, Seiton, Seiso, Seiketsu, Shitsuke, and Safety) to improve neatness and work safety in the production environment of PT. Adonia Footwear Indonesia has challenges faced, namely a poorly organized work area, lack of attention to cleanliness, and minimal employee discipline in using personal protective equipment. This field experience practice aims to integrate the theory obtained during lectures with real practices in the industrial world, especially in the implementation of the 6S work culture. Using a qualitative descriptive method with a mentoring approach that includes initial observation, interviews, documentation and Literature Study. The results of the activity show that the implementation of 6S has a positive impact on the condition of the work environment. The production area becomes neater and cleaner, employee awareness of the importance of work discipline increases, and the risk of work accidents can be minimized. Therefore, mentoring for the 6S work culture has proven effective in supporting the creation of a productive, safe, and sustainable work environment in the shoe industry sector.